Global Development in the Arctic International Cooperation for the Future - Mineev, Andrey; Bourmistrov, Anatoli; Mellemvik, Frode (Routledge Explorations in Development Studies, 2023)
Viewing the Arctic as a key region for global development in the 21st century, this book offers a cross-disciplinary conceptual framework for understanding what international cooperation is, why it is difficult and what kind of alternative views can apply in the Arctic. Written by Arctic experts, the book presents major trends and scenarios for international cooperation in the Arctic up to 2035 and future prospects for international cooperation in the Arctic in various sectors: energy, business and economy, transportation and logistics, climate change, diplomacy and security, culture, innovations, higher education and research. Implications of the scenarios for global development are discussed in the light of the United Nations Agenda for Global Development and Sustainable Development Goals. The book offers a cross-disciplinary conceptual framework of international cooperation in the Arctic and discusses implications of this framework for global development. Filling the gap in analytical understanding of international cooperation, this book will be of interest to academics, students and professionals concerned with global development and the Arctic region.